The promise of lifelong learning in the digital age for Orang Asli in Malaysia - Mohd Salim, Mohd Nur Fitri; Halim, Nurul Syafawani; Mohd Nor Rizan, Mohd Ikram; Mohd Salim, Mohamad Safwat Ashahri; Mohamad Shah, Dianna Suzieanna (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Learning has become a necessity in the modern era, with education increasingly accessible beyond classrooms and to all ages, as reflected in Malaysia’s Education Blueprint (2013–2025). However, the Orang Asli of Peninsular Malaysia face significant barriers to lifelong learning, especially in remote and digital contexts. Limited internet access, high costs of devices, and inadequate electricity have excluded many children and adults from online learning, a situation worsened during the COVID-19 pandemic. Moreover, digital content often ignores indigenous languages, culture, and practical learning needs, while effective strategies like visually oriented, group-based approaches are underutilized, further marginalizing these communities.